An intelligent recursive feature reduction methods for efficient classification of medical blogs - E A, Neeba; S, Koteeswaran (International Journal of Engineering and Technology, 2018)
Nowadays people express themselvesin the form of weblogs attracting and benefiting users in their perspective. Blogs are maintained by individual users with specific software reporting activities that removing all possible barriers and developing learning blogs. Blogs together forms a linked community as blogosphere. Procuring information from these blogs has become very tough due to the intense growth of blogs. The proposed system classifies and compiles the blog ensuring appropriate chemo taxis analysis and reporting. These data preparation and analysis helps the healthcare organizations to solve many health related problems and identify new improvements. The movement of organism to chemical stimulus is recognized in chemo taxis. Chemo taxis is subverted in cancer phases. Weblogs not only manage and organize these data but also reduces the time required for data gathering, acquisition, analysis and reporting.
Keywords: Blog Classification; Bagging; Logitboost; Adaboost; BFO and PSO